(untitled) (Marketing Journal, 2025)
This article explores the application of the ADALINE (Adaptive Linear Neuron) model in personal finance, emphasizing its role in improving decision -making accuracy. ADALINE, introduced by Bernard Widrow and Ted Hoff in 1960, utilizes gradient descent to it eratively adjust weights, enabling it to adapt to financial patterns dynamically. The study demonstrates how ADALINE enhances financial management by optimizing budgeting, saving, and expenditure decisions. Experimental results confirm that ADALINE minimiz es prediction errors over time, making it a valuable tool for managing complex financial systems. Despite its reliance on linear relationships, ADALINE proves to be a powerful approach for adaptive financial decision -making.